Peningkatan Market Share Perbankan Syariah Melalui Konversi - Ma'mun Nawawi; Elsa Elsa; Irmatul Hasanah (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten, 2023)
Abstract Indonesia is one of majority Islamic countries. It becomes the strength of the state in supporting economic development especially through Islamic banking. This research deals with strategy analysis of rising market share of Islamic banking with conversion. This research is also using qualitative approach by using library research method. Dual-banking system has been applied by Bank Indonesia. This encourages Indonesian banking to do conversion as the one of the efforts to rise market share. It is considered effective and significant since Sharia banking is turning of vision and mission based on Islamic law. As a result, it would be an increasing of market share for Indonesian society with the majority are Muslim. Keywords: Market share, Conversion, Sharia banking Abstrak Indonesia memiliki penduduk dengan mayoritas beragama Islam. Hal ini merupakan salah satu potensi untuk mendukung perkembangan ekonomi Islam di Indonesia khususnya melalui perbankan syariah. Penelitian ini bertujuan untuk menganalisis strategi peningakatan market share perbankan syariah melalui konversi. Penelitian ini menggunakan pendekatan kualitatif dengan jenis library reaserch. Setelah Bank Indonensia menerapkan dual-banking system perbankan Indonesia mulai melakukan konversi sebagai upaya untuk meningkatkan market share. Hal ini dinilai sangat efektif dan signifikan karena bank syariah hasil konversi merubah visi misi serta kegiatan operasional berdasarkan syariat islam. Hal ini dinilai dapat meningkatkan market share perbankan syariah pada masyarakat Indonesia yang mayoritas beragama Islam. Kata kunci : Market share, Konversi, Perbankan Syariah